PERMINTAAN UDANG VANNAMEI (Litopenaeus vannamei ) DI KELOMPOK PEMBUDIDAYA UDANG AT-TAQWA PACIRAN LAMONGAN - Wachidatus Sa'adah; Khiqotul Milah (Universitas Galuh Ciamis, 2019)
This research was conducted in order to know the price of shrimp vannamei and demand of shrimp vannamei at every season. This research was conducted in group of fish farmer of At-Taqwa Paciran Village, Paciran Sub-District, Lamongan Regency. The method used in this research is qualitative method. From the research results that the price greatly affects the demand for the domestic market while for the foreign market has no effect